Customer Relationship Management Theory and Research in the New Millennium: Directions for Future Research. Issue 4 (1st October 2016) - Debnath, Rajarshi; Datta, Biplab; Mukhopadhyay, Susmita
ABSTRACT: This article focuses on the research conducted in customer relationship management (CRM) from 2000 to 2014 in six top-tier academic publishing journals: Journal of Relationship Marketing, Journal of Marketing, Marketing Science, Journal of Marketing Research, Journal of Advertising Research, and Journal of Consumer Research . A total of 371 research papers related to CRM have been published in these six journals from 2000 to 2014. Five subject headings/keywords (i.e., customer relationship management; marketing; sales, service and support; information systems (IS); information technology (IT)) have been taken into consideration, from which 196 research papers have been reviewed. The theories used in these papers are discussed, as well as possible directions for future research in CRM.